Dampak Kenaikan Harga Minyak Bumi Terhadap Permintaan Cpo Untuk Biodiesel Dan Beberapa Aspek Pada Industri Kelapa Sawit Indonesia - Veryady Purba, Jan Horas (Jurnal Ilmiah Ranggagading (JIR), 2012)
Indonesia is the biggest palm oil producer and exporter in the world. In 2008, Indonesia contributed 34.3% of total palm oil world production and 84.6% of production was exported as crude palm oil (CPO). In the worldâs market, the growth of palm oil consumption and import were 9.66%/year and .34%/year. In supply side, palm oil production and export increased 7.94%/year and 9.55%/year respectively. It reflected global excess demand which influence palm oil price in world market, 1.69%/year. Demand for Indonesian CPO also to fulfill the raw material for energy. This situation will influence several aspects in Indonesian palm oil industry, in order to ensure the availability of palm oil to fulfill national necessity for cooking oil industry and bio diesel industry. The objectives of this study is to analyze (a) the correlation between world petroleum oil price with CPO world price, (b) the effect of petroleum oil price toward domestic palm oil demand, (c) the effect of petroleum oil price for 18,71% toward several aspects in Indonesian palm oil industry by econometric simulation. An econometric approach was applied in this study by using annual data 1979-2008 periods. The findings of the study show that (a) since 2000 there was the strong correlation between world petroleum oil price with CPO world price, that reflect that CPO is used for raw material of bio diesel industry; (b) petroleum oil price positively influenced domestic palm oil demand, and (c) the rise of world petroleum oil price will affect the domestic cooking oil industry, i.e. the cooking oil supply will decrease, and the cooking oil price will increase due to the lack of CP O for cooking oil industry, while the bio diesel industry was start to grow.